Intergenerational justice - Gosseries, Axel.; Meyer, Lukas H. (Oxford : Oxford University Press, 2009)
From combating climate change to ensuring proper funding for future pensions, concerns about ethics between generations are everywhere. In this volume 16 philosophers explore the wide-ranging and diverse topic of intergenerational justice.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political ethics; Intergenerational relations; Justice